(untitled) (American Journal of Pedagogical and Educational Research, 2022)
The article describes the history of archaeological research in South Khorezm. The history of the research is divided into two main periods and analyzed. It is shown that the studies conducted during these periods were interconnected and the main achievements of each period are shown.